2020
DOI: 10.1039/c9en01040h
|View full text |Cite
|
Sign up to set email alerts
|

Lateral size dependent colloidal stability of graphene oxide in water: impacts of protein properties and water chemistry

Abstract: Whether the stability of GO was related to lateral size depended on the protein type and concentration and solution chemistry conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…More recently, it was also demonstrated that GO materials displaying different lateral sizes and functional groups exhibited different interactions with BSA in aqueous medium. In this case, the water parameters such as ionic strength, solution pH, protein structure and concentration, had a pivotal influence on these nano–bio interactions [ 13 ]. Liu et al (2019) studied the protein corona formation of GO in aqueous medium containing divalent cations (i.e., Ca 2+ and Mg 2+ ), concluding that an increase in ionic strength under neutral pH conditions resulted in stronger binding between human serum albumin (HSA) and GO, as well as a more compact HSA protein layer (corona) on the GO, indicating an important role of electrostatic interactions in controlling HSA–GO complexes [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was also demonstrated that GO materials displaying different lateral sizes and functional groups exhibited different interactions with BSA in aqueous medium. In this case, the water parameters such as ionic strength, solution pH, protein structure and concentration, had a pivotal influence on these nano–bio interactions [ 13 ]. Liu et al (2019) studied the protein corona formation of GO in aqueous medium containing divalent cations (i.e., Ca 2+ and Mg 2+ ), concluding that an increase in ionic strength under neutral pH conditions resulted in stronger binding between human serum albumin (HSA) and GO, as well as a more compact HSA protein layer (corona) on the GO, indicating an important role of electrostatic interactions in controlling HSA–GO complexes [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, BSA has been considered as a model protein for assessing the fate of graphene oxide and other nanomaterials in the aquatic environment and colloidal nano-interactions with dissolved organic matter, such as humic substances [ 9 , 10 , 11 , 12 ]. Recently, Sun et al (2020) demonstrated that both protein structure and concentration are determinants for GO stability in aquatic environments, and that GO lateral size and solution chemistry are also crucial factors [ 13 ]. Despite these findings, there is a lack of systematic understanding of the protein corona formation on GO and its impacts on aquatic systems, such as ecotoxicological effects during combined exposure with other pollutants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high dose of s -GOs induced more obvious effect on glomerulus than l -GOs might be related with their different renal clearance pathway. s -GOs could be renal excreted mainly via the glomerular filtration, due to that the s -GOs keep better stability than l -GOs in the biological medium and they could resist the impacts of relatively higher concentrations of proteins and salts [ 42 ], while the l -GOs were predominately excreted via proximal tubular secretion. In addition, the more obvious effect on glomerulus by s -GOs might be related with their interaction with the renal different types of cells during glomerular filtration, such as renal glomerular endothelial cells and podocytes, which need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 OVA has 32 lysine and 15 arginine groups, much less than the 67 lysine and 26 arginine groups carried by BSA. 50 Therefore, OVA carries more negative surface charges than BSA, and the other properties of OVA are similar to the properties of BSA. In addition, the measured zeta potentials of TiO 2 with/without protein are presented in Fig.…”
Section: Characterization Of Proteins and Tio 2 Npsmentioning
confidence: 99%
“…34,[46][47][48][49] However, there is little literature on the effect of proteins with different molecular weights and surface charges on the aggregation and transport of NPs. 50 Therefore, to further accurately predict the influence of complex proteins on the fate and mobility of NPs in the environment, it is important to study the impact of different molecular weights and surface charges of proteins on the fate of NPs in the subsurface environment.…”
Section: Introductionmentioning
confidence: 99%